Culture, Pricing Strategy, and Color on Consumer Preferences in Purchasing (Jurnal Manajemen Bisnis, 2026)
This study examines the influence of culture, pricing strategies, and color on consumer preferences for fast food among Hisana Fried Chicken consumers in Makassar. The research design is quantitative, with a causal-associative approach. Data were collected by distributing questionnaires to consumers, using a Likert scale, and were processed using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS version 4.0. The results showed that culture had a positive but insignificant effect on consumer preferences. Conversely, pricing strategies and the role of color partially have a positive, significant impact on consumer preferences in fast-food purchases. These findings confirm that pricing strategies and visual elements, such as color, play an essential role in shaping consumer purchasing decisions. This study provides a theoretical contribution to consumer behavior research by applying the Stimulus-Organism-Response (S-O-R) theory, and a practical contribution to fast-food restaurant management by formulating more effective marketing strategies based on price and visual design to increase customer preference and loyalty.